Antenna Polarization Optimization for Target Detection in Non-Gaussian Clutter - Xu Cheng; Yong-zhen Li; Xue-song Wang (International Journal of Antennas and Propagation)
Adaptive polarization design of radar antenna has recently become the focus of attention in radar polarization community. A polarimetric detector against non-Gaussian clutter with transmitter polarization optimization has been proposed in this paper. First, the radar data model including the realistic dependence of the clutter on the transmitted polarization is introduced. Then the polarimetric detector with transmitter polarization optimization is developed. By employing the simulation, we demonstrate that the polarization waveform optimization can bring the significant performance gain on target detection as compared to the conventional full-polarization approach. Besides, jointly optimizing transmitter and receiver polarization to form a scalar measurement is confirmed not to achieve a better detection performance than vector measurement with only transmitter polarization optimization.